A Frailty Instrument for primary care for those aged 75 years or more: findings from the Survey of Health, Ageing and Retirement in Europe, a longitudinal population-based cohort study (SHARE-FI75+). - ROMERO-ORTUNO, ROMAN (My University, 2014)
Objective To create and validate a frailty assessment tool for community-dwelling adults aged ≥75 years. Design Longitudinal, population-based study. Setting The Survey of Health, Ageing and Retirement in Europe (SHARE). Participants 4001 women and 3057 men aged ≥75 years from the second wave of SHARE. 3325 women and 2587 men had complete information for the frailty indicators: fatigue, low appetite, weakness, observed gait (walking without help, walking with help, chairbound/bedbound, unobserved) and low physical activity. Main outcome measures The internal validity of the frailty indicators was tested with latent class analysis, by modelling an underlying variable with three ordered categories. The predictive validity of the frailty classification was tested against 2-year mortality and 4-year disability. The mortality prediction of SHARE-FI75+ was compared with that of previously operationalised frailty scales in SHARE (SHARE-FI, 70-item index, phenotype, FRAIL). Results In both genders, all frailty indicators significantly aggregated into a three-category ordinal latent variable. After adjusting for baseline age, comorbidity and basic activities of daily living (BADL) disability, the frail had an OR for 2-year mortality of 2.2 (95% CI 1.2 to 3.8) in women and 4.2 (2.6 to 6.8) in men. The mortality prediction of SHARE-FI75+ was similar to that of the other SHARE frailty scales. By wave 4, 49% of frail women (78 of 159) had at least one more limitation with BADL (compared with 18% of non-frail, 125 of 684; p<0.001); in men, these proportions were 39% (26 of 66) and 18% (110 of 621), respectively (p<0.001). A calculator is supplied for point-of-care use, which automatically replicates the frailty classification for any given measurements. Conclusions SHARE-FI75+ could help frailty case finding in primary care and provide a focus for personalised community interventions. Further validation in trials and clinical programmes is needed
PUBLISHED
Keywords: Frailty